JONES TENDON TRANSFER MODIFICATION WITH ERWIN RAMAWAN TECHNIQUE - Erwin Ramawan; Teddy Heri Wardhana; Ansari Rahman (Journal Orthopaedi and Traumatology Surabaya, 2019)
Background: Drop hand is a clinical manifestation of radial nerve lesion that cause hand dysfunction. Jones tendon transfer is one of the therapeutic modalities in overcoming it with many modifications, but there is still no mutual agreement for which technique is the best. One of them is the Erwin Ramawan technique. The purpose of this study was to determine the differences in results before and after tendon transfer surgery with the Erwin Ramawan technique in patients with radial nerve lesions.Methods: Retrospectively, we evaluated patients with high-type lesions of radial nerve carried out by tendon transfer surgery using Erwin Ramawan, to reroute PL to EPL, so the thumb can do abduction and extension, then the FCR tendon is positioned parallel to the ECRB and EDC, then connected 45° direction. The outcome was evaluated using the DASH score and with the Robert G. Chouinard method.Results: The average DASH score in patients with high-type lesions of  radial nerve before surgery 56.83 ± 16.69 had a significant improvement (p <0.05) after tendon transfer surgery with Erwin Ramawan technique to 32.00 ± 11.88. Functionally, dorsiflexion from wrist postoperative is 75.00 ± 10.00 (excellent), palmarflexion 52.00 ± 24.65 (excellent). For finger, the metacarpophalangeal extension reaches 166.00 ± 19.49 (good). The distance from the fingertip to metacarpophalangeal crease is 0.10 ± 0.22 (good). On thumb, abduction reaches 40.00 ± 15.81 (excellent), interphalangeal extension 166.00 ± 11.44 (good).Conclusion: Based on these results, we found significant clinical differences before and after tendon transfer with the Erwin Ramawan technique.